Analisis Peraturan Bupati Sampang Nomor 27 Tahun 2021 tentang Pemberhentian Penjabat Kepala Desa (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The author analyzes Sampang Regent Regulation Number 27 of 2021 concerning Guidelines for Candidacy, Election, Appointment, Inauguration, and Dismissal of Village Heads, focusing on ambiguity regarding the dismissal of Acting Village Heads. Currently, around 50 villages in Sampang Regency are led by Pj. Kades who are being evaluated, but the regulation does not contain clear provisions regarding their dismissal. This creates legal uncertainty and potential turmoil in society. The author uses a normative method with case studies based on primary and secondary legal materials, such as the relevant Regent Regulation. The results of the analysis show that the lack of clarity in the rules for the dismissal of the Acting Village Head poses a risk of abuse of power and politicization, especially because the evaluation results are not transparent. Therefore, it is necessary to revise the Regent Regulation to provide a clear legal basis for the dismissal of the Acting Village Head, in order to create legal certainty in the village government in Sampang Regency.